Konsep Teknik Penyusunan Tes Maharah Qira’ah Pada Pembelajaran Bahasa Arab - Nelvianti, Lidia (Universitas Islam Negeri Imam bonjol Padang, 2024)
Maharatul Qiraah or reading skills is one of four skills, including maharahatul istima', maharahatul kalam, and maharatul kitabah. Maharah Qiraah is one of the basic skills in a foreign language which is also important, this is because reading skills are classified as active receptive abilities, and this ability is to understand the language spoken by other parties (decoding process). In Maharah Qira'ah learning, teachers are required to choose appropriate and effective learning methods, because the choice of method plays a very important role in making things easier for teachers and also making things easier for students in the teaching and learning process. This research uses the Qualitative Library Research research method. And this article also aims to describe how to prepare the correct Maharah Qira'ah test for learning Arabic. Having guidelines for preparing the Maharah Qira'ah test will make it easier for teachers to find appropriate and effective learning methods for learning Maharah Qira'ah. From the research results, it was found that this method was able to improve students' reading skills in learning maharah qira'ah